Evaluation of clinico-radiological factors affecting morbidity and mortality in peptic ulcer perforation surgery - Yeni, Mustafa; Kartal, Murat; Kalaycı, Tolga (The European Research Journal, 2022)
Objectives: Peptic ulcer perforation (PUP) remains a surgical emergency with high early period morbidity and mortality. In this study, it was aimed to evaluate clinico-radiological factors affecting morbidity and mortality in peptic ulcer perforation surgery. Methods: Patients who were operated for PUP at Erzurum Regional Training and Research Hospital General Surgery Clinic, Erzurum, Turkey between 2010 and 2020 were selected retrospectively. The patients’ clinical and radiological parameters were retrieved from their medical records. Patients who developed complications in the 30 days after surgery were considered the morbidity-positive group, and the patients who developed mortality in the 30 days after surgery were considered the mortality-positive group. The relationship between investigated factors and morbidity and mortality was investigated with suitable statistical tests. A p value < 0.05 was considered statistically significant. Results: The study included 81 patients and, 74 (91.4%) patients were males. Complications were observed in 15 (18.5%) patients and mortality was seen in 3 (3.7%) patients in the first 30 days postoperatively. Preoperative comorbidity, low systolic blood pressure, high Boey score had negative effect on both morbidity and mortality. In addition, lower amylase levels played a protective role in both morbidity (p = 0.011) and mortality (p = 0.018). Mortality increased significantly with increasing age. However, no radiological factor affected either morbidity or mortality. Conclusions: Both morbidity and mortality increased in cases with poor clinical condition at the time of diagnosis. In addition, the mortality rate was higher in patients with comorbidities and postoperative complications.